Surgical outcomes of temporary short-segment instrumentation without augmentation for thoracolumbar burst fractures - Aono, Hiroyuki; Tobimatsu, Hidekazu; Ariga, Kenta; Kuroda, Masayuki; Nagamoto, Yukitaka; Takenaka, Shota; Furuya, Masayuki; Iwasaki, Motoki (Injury, 2016)
Short-segment posterior spinal instrumentation for thoracolumbar burst fracture provides superior correction of kyphosis by an indirect reduction technique, but it has a high failure rate. We investigated the clinical and radiological results of temporary short-segment pedicle screw fixation without augmentation performed for thoracolumbar burst fractures with the goal of avoiding treatment failure by waiting to see if anterior reconstruction was necessary. We studied 27 consecutive patients with thoracolumbar burst fracture who underwent short-segment posterior instrumentation using ligamentotaxis with Schanz screws and without augmentation. Implants were removed approximately 1 year after surgery. Neurological function, kyphotic deformity, canal compromise, fracture severity, and back pain were evaluated prospectively. After surgery, all patients with neurological deficit had improvement equivalent to at least 1 grade on the American Spinal Injury Association impairment scale and had fracture union. Kyphotic deformity was reduced significantly, and maintenance of the reduced vertebra was successful even without vertebroplasty, regardless of load-sharing classification. Therefore, no patients required additional anterior reconstruction. Postoperative correction loss occurred because of disc degeneration, especially after implant removal. Ten patients had increasing back pain, and there are some correlations between the progression of kyphosis and back pain aggravation. Temporary short-segment fixation without augmentation yielded satisfactory results in reduction and maintenance of fractured vertebrae, and maintenance was independent of load-sharing classification. Kyphotic change was caused by loss of disc height mostly after implant removal. Such change might have been inevitable because adjacent endplates can be injured during the original spinal trauma. Kyphotic change after implant removal may thus be a limitation of this surgical procedure.